Russel’s score and diabetes mellitus type 2 “finding the association”: a cross sectional study from one of the districts in Bihar, India - Kumar, Neeraj; Rana, Rishabh Kumar; Kumar, Vivek; ., Rohit; Sinha, Pramod Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes has been on the rise since last decade or so with prevalence rate changing as more research is being done. India is one of the most burdened country from diabetes specially type 2. With changing life style other diseases are also on the rise and evidence is being generated to find tangible association. One such disease is periodontitis. As evidence from the State of Bihar for association between periodontitis and diabetes mellitus is negligible this study was conducted to find the same. Methods: A cross sectional observational study in community settings was done for three months on 200 diabetic willing participants. Data was generated using a semi structured pretested questionnaire. Data analysis was done using SPSS version 22.0 and statistical measures of central tendency like mean, mode, median and standard deviation were used. For establishing association chi square tests were used. P values<0.05 were considered to be statistically significant. Results: 61.5% of the participants were male while 65.5% were from rural area. The study population was on an average on the older side with a mean age of 52±12.15 and on the bulky size with a BMI of 28.85±4.08. Authors got the average Russel’s score to be 1.1±1.79. The mean blood sugar level for fasting was 146.40±59.99 and post prandial levels was 211.59±82.49. A Russel score category of established periodontal disease and terminal disease was present in 77.5% of participants having an altered fasting blood sugar level. Majority of the males had established periodontal disease and terminal disease. Patients with elevated postprandial blood sugar levels had more established periodontal disease and terminal disease. Conclusions: Oral health is definitely associated with diabetes mellitus type 2 and its other factors like duration, glycaemic control, blood sugar levels etc. Public awareness regarding this is minimal. More research and awareness regarding this will help in keeping the diabetic population healthy.